Estudo experimental do comportamento de um hidrociclone com cone e cilindro filtrantes - Salvador, Fernanda Falqueto (2013)
Hydrocyclones are equipments destined to solid-liquid separation broadly used in industry due to its advantages, including compact geometry, high separation efficiency, simple maintenance and low cost. Depending on the user desired finality (concentration or classification), it is possible to potentiate the hydrocyclones performance by the simultaneous use of new unit operations to hydrocycloning, for example, the filtration. The filtering hydrocyclone was an equipment developed and improved by FEQUI/UFU researchers. In this way the objective of this work was to experimentally study the effect of incorporating a porous cylinder and cone, together or separately, to the optimized geometry conventional hydrocyclone (H11). Experiments were done with aqueous suspension of phosphate rock in three different permeability values for the porous media and three underflow diameters. According to the main results, the hydrocyclones HCiF, HCoF and HCiCoF showed mean decrease in the energetic consume of 13, 32 and 35% respectively, in comparison to conventional hydrocyclone (HCon), in the lowest permeability used for the filtering medium. However the underflow-to-throughput ratio of the hydrocyclones HCiF, HCoF and HCiCoF increased in relation to the conventional hydrocyclone (HCon), regardless the permeability or the underflow diameter used. About the total efficiency of the filtering equipments, little differences in relation to the conventional separator were observed, and can be said that this variable remained practically constant for the same operational condition. From the experimental data it was possible to obtain the project equations and the total efficiency curves even for distinct granulometries of each hydrocyclone studied. In summary can be concluded that in the case of filtering hydrocyclones, it is not advisable to use filtering medium with permeability higher than 2,0.10-6 m2 because, in energetic terms, they will consume more energy than the conventional hydrocyclone, and in terms of separation they will be practically equal to the conventional separator.